Digital divides in telehealth accessibility for cancer care in the United States - Lingbo Liu; Tracy Onega; Erika L. Moen; Anna N. A. Tosteson; Rebecca E. Smith; Qianfei Wang; Lauren Cowan; Fahui Wang (npj Digital Medicine)
Abstract Telehealth has been promoted as a solution to spatial healthcare access barriers, yet its role in addressing cancer care disparities remains uncertain, particularly in the context of digital divides in broadband availability and affordability. This study assessed spatial and telehealth accessibility to cancer care across 33,499 ZIP Code Tabulation Areas (ZCTA) in the United States using the two-step floating catchment area (2SFCA) and two-step virtual catchment area (2SVCA) methods, respectively. Incorporating physician locations, cancer incidence, travel time based on transportation networks, and broadband coverage and subscription rates, we found that accessibility declined from urban to rural areas and was lower in ZCTA with greater socioeconomic deprivation. Areas with higher proportions of Black and Hispanic populations showed modestly higher access scores, yet a three-way interaction among rurality, deprivation, and racial ethnic composition revealed compounded disadvantages. Telehealth reduced but did not eliminate these gaps, highlighting how its reliance on digital infrastructure may both alleviate and intensify disparities in cancer care access.